Fibrostenotic Inflammatory Bowel Disease (Springer International Publishing, 2018)
This book provides a comprehensive account of the pathogenesis and treatment of intestinal fibrosis, covering both the clinical and molecular aspects of the disease. It begins by describing the epidemiology and genetics of fibrostenosing IBD in Crohn's disease and Ulcerative colitis as well as the epigenetics and cellular and molecular mechanisms of the disease. Readers will obtain an in-depth overview of the disease from biomarkers and histology to surgical intervention, imaging and current and future drug therapies. Medical management of fibrosis, endoscopy and imaging as well as surgical approaches are all discussed. Through the links to videos contained in the book, the reader will become familiar with interventional procedures such as endoscopic balloon dilation and surgical techniques for stricturing IBD, such as resection and strictureplasties. This is an indispensable volume for anyone working on fibrostenotic IBD, such as gastroenterologists, internists, radiologists, colorectal surgeons, pathologists and researchers. It has been written by a team of top experts from North America, Asia and Europe. .